Pendampingan Pembuatan dan Penggunaan Alat Permainan Edukatif (APE) Untuk Guru PAUD: Bahasa Indonesia - Almira Rahmatu Syahida; Rika Purnamasari (Institut Agama Kristen Negeri Kupang, 2024)
This article aims to provide assistance to PAUD teachers in making and using educational game tools for early childhood. This research began with observations of PAUD schools in Cihanjawar Village, Bojong District. The problems found in this study are the lack of availability of educational game tools in PAUD institutions and the teacher’s lack of understanding regarding how to use and apply them to learning activities. Therefore, it is necessary to carry out training and assistance regarding how to make and use educational game tools for PAUD teachers in Cihanjawar Village. The type of research used is Participatory Action Research (PAR) with presentation, demonstration, and direct practice methods. This research is expected to broaden knowledge and understanding of the importance of APE for early childhood and improve the skills of PAUD teachers in making APE from simple materials in the surrounding environment.